2011
DOI: 10.1016/j.bbadis.2011.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Severe dysfunction of respiratory chain and cholesterol metabolism in Atp7b−/− mice as a model for Wilson disease

Abstract: Wilson disease (WD) is caused by mutations of the WD gene ATP7B resulting in copper accumulation in different tissues. WD patients display hepatic and neurological disease with yet poorly understood pathomechanisms. Therefore, we studied age-dependent (3, 6, 47weeks) biochemical and bioenergetical changes in Atp7b(-/-) mice focusing on liver and brain. Mutant mice showed strongly elevated copper and iron levels. Age-dependently decreasing hepatic reduced glutathione levels along with increasing oxidized to red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
64
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 30 publications
10
64
0
1
Order By: Relevance
“…Previous reports indicated that a defected ATP7B, one of the major copper-delivery targets of Atox1, could lead to altered COX activity in mice 37 . We found that the activities of COX (units ml −1 ) in H1299 cells in the presence of DC_AC50 are significantly lower than those of the control (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports indicated that a defected ATP7B, one of the major copper-delivery targets of Atox1, could lead to altered COX activity in mice 37 . We found that the activities of COX (units ml −1 ) in H1299 cells in the presence of DC_AC50 are significantly lower than those of the control (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The high metabolism of neurons produces a lot of oxidative stress, demanding a high-capacity system for maintaining the redox homeostasis. Intracellular Cys seems to be the rate-limiting factor for GSH synthesis in neurons (Griffith, 1999), and oxidative stress and altered GSH levels have been implicated in several diseases including multiple sclerosis, Wilson disease, Parkinson’s disease (PD), Alzheimer’s disease (AD) and amyotrophic lateral sclerosis (ALS) where protein redox state has been described in mechanisms of redox-regulated cell death, (Dringen, 2000, Uttara et al, 2009, Haider et al, 2011, Sauer et al, 2011, McBean et al, 2015). …”
Section: Functionmentioning
confidence: 99%
“…These early changes in lipid metabolism are maintained throughout the course of the disease as indicated by the analysis of the mRNA levels and serum lipid profiles at the later stages of the disease (80). Follow-up studies revealed that the sterol metabolism in a brain of young Atp7b-/-mice was also dysregulated, with cholesterol, 8-dehydrocholesterol, desmosterol, 7-dehydrocholesterol, and lathosterol all being highly increased (81,82). It should be noted that the main cholesterol-sensing pathway that involves proteolysis and nuclear localization of SREBP2 transcription factor is not impaired in Atp7b -/-hepatocytes (79).…”
Section: Copper Overload In Wilson's Disease Markedly Alters Lipid Mementioning
confidence: 99%